The Lawfulness of Using Copyrighted Works for Generative AI Training : A Case Study of a US Lawsuit against OpenAI and Perplexity AI - Ismantara, Stefany; Silalahi, Wilma (JUSTISI, 2025)
Copyright protection in Indonesia is governed by Law No. 28 of 2014 (Law 28/2014), encompassing moral and economic rights. This law imposes limitations on the use of works for education, law enforcement, or technological development as long as such use does not harm the legitimate interests of the rightholder. The development of generative AI (GAI) poses challenges in determining the legality of using copyrighted works for GAI training. This study examines copyright regulations concerning GAI through normative, conceptual, and comparative legal approaches, including case studies on lawsuits against OpenAI and Perplexity AI. The findings indicate that the legality of using copyrighted works depends on the data input process and output (responses). Data scraping is considered an economic right of the rightholder, classified as reproduction under Article 9 of Law 28/2014. If such acts are conducted without the rightholder’s consent and for commercial purposes, they are deemed unlawful under Indonesia’s current copyright law. GAI outputs may also infringe copyright if: (1) the source is not cited, violating Article 7 on copyright management information; (2) substantial portions of the work are reproduced, violating the rightholder's economic rights under Article 9; or (3) the work is distorted in a way that harms the rightholder’s honor, infringing on moral rights under Article 5. To accommodate AI development, specific regulations integrating AI transparency principles outlined in SE Kominfo 9/2023 are required. These regulations could include obligations for AI companies to release summaries of training datasets, include Uni EropaLAs that define the responsibilities of AI developers and users, and provide disclaimers regarding AI's limitations. Regarding the fulfillment of rightholders’ economic rights, a non-exclusive blanket license through Collective Management Organizations (CMOs) as stipulated in Permenkumham 15/2024 is necessary. These regulations should be synchronized with related policies to establish legal certainty that adapts to technological advancements.